Notifiche
Cancella tutti

Integrale definito

  

1
98
Autore
2 Risposte



2

(√x - 1)^2/x=

=(x - 2·√x + 1)/x =

=- 2/√x + 1/x + 1 

∫(2/√x)dx =

=4·√x

∫(1/x) dx = LN(x)

∫ 1 dx = x

Quindi:

∫((√x - 1)^2/x) dx =

= LN(x) + x - 4·√x

Valutato in x = 4:

LN(4) + 4 - 4·√4

Valutato in x = 1:

LN(1) + 1 - 4·√1 = -3

Quindi:

LN(4) + 4 - 4·√4 + 3 = 2·LN(2) - 1

 

 



2

∫[x + 1 - 2 radice(x)] / x  dx =

=∫(x / x) dx + ∫(1/x) dx  -  2∫ [radice(x) / x] dx =

= ∫1 * dx + ∫(1/x) dx  - 2 ∫ radice(x/x^2) dx    calcolati tra 1 e 4

∫1 dx  = x ;  tra 1 e 4;

∫(1/x) dx = ln(x) ; tra 1 e 4;

- 2 ∫ radice(x/x^2) dx  = - 2 ∫radice(1/x) dx = - 2 ∫ [(x^-1)^1/2 dx =

= - 2 ∫ (x^-1/2) dx = - 2 * (x^1/2) / (1/2) = - 2 * 2 radice(x);    tra 1 e 4;

∫[x + 1 - 2 radice(x)] / x  dx = x + lnx - 4 radice(x) = 

 = 4 - 1 + ln(4) - ln(1) - 4 * [radice(4) - radice(1)] =

= 3 + ln(2^2) - 0 - 4 * (2 - 1) =

= 3 + 2 ln(2) - 4 * 1 = 2 ln(2) - 4 + 3 = 2 ln(2) - 1.

Ciao  @alby



Risposta
SOS Matematica

4.6
SCARICA